Development of hepatocellular carcinoma in Japanese patients with biopsy‐proven non‐alcoholic fatty liver disease: Association between PNPLA3 genotype and hepatocarcinogenesis/fibrosis progression. Issue 11 (15th December 2016) - Seko, Yuya; Sumida, Yoshio; Tanaka, Saiyu; Mori, Kojiroh; Taketani, Hiroyoshi; Ishiba, Hiroshi; Hara, Tasuku; Okajima, Akira; Umemura, Atsushi; Nishikawa, Taichiro; Yamaguchi, Kanji; Moriguchi, Michihisa; et al.
Abstract : Aim: Some patients with non‐alcoholic fatty liver disease (NAFLD) develop hepatocellular carcinoma (HCC). Patatin‐like phospholipase domain containing 3 (PNPLA3) rs738409 (encoding the I148M variant) has been associated with advanced fibrosis and HCC. We determined the risk factors for HCC, including the PNPLA3 rs738409 polymorphism, in Japanese patients with biopsy‐proven NAFLD. Methods: In this retrospective cohort study, we analyzed hepatocarcinogenesis in 238 patients. PNPLA3 rs738409 genotype was determined by allelic discrimination in 130 patients. Among them, 86 patients who were followed up for >5 years and without liver cirrhosis were analyzed to clarify the relationship between PNPLA3 genotype and long‐term changes in biomarkers. Results: Of 238 patients, PNPLA3 genotype frequencies were: CC, 0.14; CG, 0.46; and GG, 0.40. During a follow‐up period of 6.1 years, 10 patients (4.2%) with non‐alcoholic steatohepatitis developed HCC. The cumulative rate of HCC was 1.9% at the end of the 5th year and 8.3% at the end of the 10th year. Multivariate analysis identified PNPLA3 genotype GG (hazard ratio, 6.36; P  = 0.019) and fibrosis stage (fibrosis stage 3/4; hazard ratio, 24.4; P  = 0.011) as predictors of HCC development. In the long follow‐up cohort, a larger reduction in platelet count was found in the GG group ( P  = 0.032) despite a larger reduction in alanine aminotransferase ( P  = 0.023) compared to that in the CC/CG group. Conclusions: In Japanese patients with NAFLD, severe fibrosis and PNPLA3 GG genotype were predictors of HCC development, independent of other known risk factors. Patients with the PNPLA3 GG genotype have the potential for a decreased platelet count, even when alanine aminotransferase levels are well controlled.